Diversity of Wetland Birds around the Koshi Barrage Area - Chhetry, D. T. (Our Nature, 2007)
Koshi Barrage area comprises of a large reservoir, marshlands channels, floodplain, reed beds etc. which support fascinating birdlife. The present paper deals with the studies of wetland birds diversity of the Koshi Barrage area. Altogether 98 species of wetland birds belonging to 60 genera and 18 families were recorded. Key words: Koshi Barrage, Wetland birds doi:10.3126/on.v4i1.507 Our Nature Vol. 4(1) 2006 pp91-95